Advancing Power System Resilience through Information Network Security - Lin, Ziyu (International Journal of Computer Science and Information Technology, 2024)
With the continuous development of informatization in the power industry, the importance of information security is becoming more and more prominent, and the test faced by the increasingly severe. The whole paper analyzes several major sources of threats to the security of the power system and the problems involved in LAN security management, and from the information security technology and management puts forward its ideas and methods to enhance the information security protection capability of the smart grid, enhance the information security of the autonomous and controllable capacity, and to enhance the information security of the power industry.